PENGELOLAAN KTSP SEKOLAH DASAR MODEL KOTA LUBUKLINGGAU - Endang Budiman; Rambat Nur Sasongko; Safnil Safnil (UNIVERSITAS BENGKULU, 2017)
The objective in this research is desevice the management of the curriculum in schools Basic Pilot of Lubuklinggau. The general objective of this study was to evaluate the suitability of the curriculum in primary school curriculum management Lubuklinggau in implementing the evaluation of learning curriculum specifically 2006. The method used in this research using questionnaires, interviews and documentation. The results of the questionnaire study states that the planner learning device KTSP scored 33.33, and on the implementation of the scores 34, and the evaluation results to get a score of 30 and an average of 32.44, it can be concluded already meet the standards. Researchers in this research can be concluded that the planning, implementation and evaluation of results have met the standards.